DYNAMICS OF TUNISIAN POLYGAMY LAW IN GENDER PERSPECTIVE - Chusnayaini, Ayyus Sahidatul (Fakultas Syariah, 2014)
This research aims to answer the problem of dynamics of Tunisian polygamy law in gender perspective. The method was used in this study was the type of normative research with collaboration of the historical, statute and conceptual approach. The results of determines that the dynamics of polygamy law is a great revolution in Tunisia. There are several factors that influence the dynamics: understanding of religion; secular ideology; socio-cultural; political; and education. This dynamics can be seen from the third period of legal development, namely: a) the period of preindependence b) The period after independence c) the period of the revolution (nowadays). There are some issue about the discourse of law legalizing on banning polygamy law in Tunisia. The dynamics of polygamy law that occurred in the period after independence indicates a progression of the effort from Tunisian State to protect the rights of women.Penelitian ini bertujuan untuk menjawab masalah dinamisasi hukum poligami di Tunisia menurut gender. Penelitian ini menggunakan metode pendekatan penelitian normatif dengan mengolaborasikan sejarah, undang-undang dan konsep. Hasil penelitian dinamika menunjukan sebuah revolusi yang besar di Tunisia. Diantara faktor-faktor yang mempengaruhi dinamika tersebut adalah: pemahaman agama; idiologi sekuler; susio-kultural; politik; dan pendidikan. Dinamika ini dapat dilihat dari 3 periode perkembangannya, yang disebut: a) periode sebelum independen; b) periode setelah independen; dan c) periode revolusi (sekarang). Ada beberapa persoalan tentang wacana hukum yang melegalkan larangan poligami di Tunisia. Dinamika hukum poligami yang terjadi setelah kemerdekaan menunjukan usaha negara Tunisia untuk meningkatkan perlindungan terhadap hak-hak wanita.